Desarrollo de una aplicación para windows de técnicas de hardening sobre sistemas operativos linux para la obtención de reportes - Benítez Buenaño, José Oswaldo (2015)
This paper grade is focused on computer audit of GNU/Linux servers and your contribution is to facilitate the work to a manager operating systems to optimize the tasks of identifying vulnerabilities through of executing commands necessary to reflect the necessary information for later analyze, and present it along with recommendations on how to mitigate risks server in the theoretical content of this project suggestions for each type of analysis is detailed. Applying techniques HARDENING regarding permissions, settings and review of LOGS, has identified the set of information needed to identify vulnerabilities in the server. For this development has been used VB.net technology, native libraries from Microsoft and additional for managing SSH protocol, using Microsoft Word for obtaining general reports and the burden of the recommendations in each type is also made analysis. The application allows the audit to 4 servers simultaneously establishing synchronous connections and is compatible with the distributions, Centos, OpenSUSE, Ubuntu, Fedora and those derived from the above, is customized analysis for each distribution due to differences in the directories and names configuration files, therefore it finally comes to a general report in .docx extension where you have the recommendations and results of analyzes that have been selected. The SCRUM methodology was chosen for the project accordingly detailed activities and their respective times and documented evidence.